Design Optimization of Structural Parameters for Inductive Magnetic Sensor. Issue 6 (April 2019) - Zhao, Jie; Wang, Zhicheng; RAYHAN Tanvir, MD; Zhou, Shumin; Huang, Hongwei
Abstract: In recent years, the national electric power industry has developed rapidly, the power system is becoming more and more perfect, the modern transmission network is constantly developing and building, the digital substation is gradually intellectualized and the fast fault location of the power system has become the main focus development of the smart grid. A magnetic induction traveling wave sensor is designed for high voltage power fault line traveling wave band frequency bandwidth, easy saturation, fast signal attenuation, poor transient characteristics and serious electromagnetic interference. The magnetic field simulation and signal analysis are carried out based on Ansoft Maxwell and Matlab software platform. The relationship between the structural parameters of the sensor and the electrical characteristics of the sensor is established by combining the theoretical research with the experimental verification. The structural parameters such as the core, the number of coil turns and the line diameter are optimized and the sensitivity of the sensor is improved and the development of the new sensor is completed. The research results show that the optimized sensor can pick up 100 KHz – 10 MHz traveling wave signal accurately and has high transmission ratio, high attenuation and strong interference suppression ability.